Private authority in tackling cross-border issues. The hidden path of integrating European energy markets - Eberlein, Burkard; Eckert, Sandra (Journal of European Integration, 2020)
We investigate private authority in European Union (EU) energy governance in order to address two research questions: First, how has authority been conferred on, and acquired by private actors? Second, to what extent has this lateral shift of authority been contested and on which grounds? The paper links the literatures on regulatory governance and private authority. This allows us to shed light on an issue that tends to be neglected in the discussion about the transfer of competencies in the energy field: the horizontal transfer of authority. In our case study about the role of transmission system operators (TSOs) in the creation of an internal electricity market, we identify three distinct settings where both the level of sovereignty-based contestation and the shift towards private authority vary. We find that private rulemaking has gained in importance due to functional expertise requirements, but also because it provides an escape route in a context of political contestation.
Created from Fastlane, Scopus look-up
Keywords: electricity; Energy policy; governance; infrastructure; private authority